1994
DOI: 10.3109/00016349409072507
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographical and hormonal description of the normal ovulatory menstrual cycle

Abstract: Vaginal ultrasonography is a practical and reliable method to monitor structural changes in the ovaries and the uterus during the menstrual cycle. The results are of clinical importance for a better understanding of the physiological changes and helpful when monitoring induction of ovulation in assisted reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 29 publications
3
53
1
2
Order By: Relevance
“…Even in empirical articles that report little luteal variation in ET, a clear, though qualitative, change in ET can be observed (Figure 2, Table 6). Research measuring ET serially is infrequent, but we have found articles that document ET via transvaginal ultrasound in Canadian (Baerwald and Pierson, 2004), Scottish (Randall et al, 1989), English (Raine-Fenning et al, 2004), and Swedish populations (Bakos et al, 1994). There are a few confounding problems with the serial measurements from the literature when it comes to assessing luteal endometrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Even in empirical articles that report little luteal variation in ET, a clear, though qualitative, change in ET can be observed (Figure 2, Table 6). Research measuring ET serially is infrequent, but we have found articles that document ET via transvaginal ultrasound in Canadian (Baerwald and Pierson, 2004), Scottish (Randall et al, 1989), English (Raine-Fenning et al, 2004), and Swedish populations (Bakos et al, 1994). There are a few confounding problems with the serial measurements from the literature when it comes to assessing luteal endometrial function.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical part of the research protocol was designed on the assumption of a good correlation between the diameter of the dominant follicle and serum concentration of estradiol [19,20,27,28]. During the follicular phase, a blood sample was taken only when the dominant follicle was visible.…”
Section: Discussionmentioning
confidence: 99%
“…The size of dominant follicles was determined by measuring one diameter in the case of a round follicle and calculating the mean of two diameters if the follicle was oval [19,20]. Two scans were performed; the first scan at the end of menstrual bleeding (day 5-7 of menstrual cycle) and the second one 4 to 5 days later (day 9-12 of the cycle).…”
Section: Participantsmentioning
confidence: 99%
“…Studies of ovulatory function in HIVseropositive women have mixed results. While anovulatory cycles are reported to occur in 5-31% of healthy women with regular menses (27,28), they were reported in 48% of HIV-infected women in one small study, with a trend to occur more in women with low CD4 cell counts (29). Another small study reported anovulatory cycles in almost one third of HIV-positive women reporting normal menses (30), but a larger study of 55 HIV-infected and 10 negative controls reported ovulatory cycles in 96% of the seropositive and 78% of the seronegative women (31).…”
Section: Menstrual Disordersmentioning
confidence: 99%